The strategic management of intellectual capital : a case study in the banking and financial services sector in Zambia - Banda, Japhet Mathias (Rhodes University, Faculty of Commerce, Department of Management, 2011)
Fundamental changes in the global economy are changing the basis of organisational competitive advantage. The challenge in attaining a competitive advantage is characterised by factors such as increased competition, market volatility, geographically dispersed operations, customer awareness, raising workforce diversity and stringent regulatory regimes. These factors have driven, and in turn have been driven by, an increasing complexity of products, services and the processes that create value, resulting in changes in the structural and functional dimensions of the organisation. Business executives and academics recognise the shift in value creating assets from the traditional land, labour and capital to intangible assets such as knowledge and information becoming the most important resources an organisation can muster.The combination and integration of intangible assets such as human resources, structural and relational resources has been grouped under the umbrella of intellectual capital. This study comprises of a single descriptive case study analysis to ascertain how intellectual capital is managed strategically to gain a competitive advantage in an organisation in the banking and financial services sector in Zambia. Based on document review and semi-structured interviews, this thesis investigated the extent to which an organisation in the banking and financial services sector in Zambia leveraged intellectual capital to gain competitive advantage. In this study it was found that there is a low level appreciation of the intellectual capital phenomenon as a strategic management tool in the participating organisation. However, the organisation has adopted aspects of intellectual capital and has implemented them successfully accounting for the organisation's competitive edge in the market.
Keywords: Intellectual capital -- Management; Intellectual capital -- Zambia; Banks and banking -- Zambia; Financial services industry -- Management -- Zambia